Pengaruh kondisi operasi proses pemekatan litium dari geothermal brine sintetis dengan metode Direct Contact Membrane Distillation (DCMD) - Dimas Bagus Galih Utomo; Vincent Sutresno Hadi Sujoto; Widi Astuti; Fika Rofieq Mufakhir; Aron Pangihutan Christian Tampubolon; Syamsumin Syamsumin; Andhika Putera Utama; Himawan Tri Bayu Murti Petrus; Mohammad Fahrurozi; Sutijan Sutijan (Jurnal Rekayasa Proses, 2023)
Ahmed FE, Lalia BS, Hashaikeh R, Hilal N. 2020. Alternative heating techniques in membrane distillation: A review. Desalination. 496(September):114713. doi:10.1016/j.desal. 2020.114713.Alkhudhiri A, Darwish N, Hilal N. 2012. Membranedistillation: A comprehensive review. Desalination. 287(January):2– 18. doi:10.1016/j.desal.2011.08.027.Baksir A, Daud K, Wibowo ES, Akbar N, Haji I. 2019. Halmahe- ra , North Maluku Province. 22.Blanco Gálvez J, García-Rodríguez L, Martín-Mateos I. 2009. Seawater desalination by an innovative solar-powered membranedistillation system: the MEDESOL project. De- salination. 246(1-3):567–576. doi:10.1016/j.desal.2008.12.005.Flexer V, Baspineiro CF, Galli CI. 2018. Lithium recovery from brines: A vital raw material for green energies with a po- tential environmental impact in its mining and proces- sing. Science of The Total Environment. 639:1188–1204. doi:10.1016/j.scitotenv.2018.05.223.H Tangkas IWCW, Astuti W, Sutijan, Sumardi S, Petrus HTBM. 2021. Lithium titanium oxide synthesis by solid-state re- action for lithium adsorption from artificial brine source. IOP Conference Series: Earth and Environmental Scien- ce. 882(1):012005. doi:10.1088/1755-1315/882/1/012005.Hartono M, Astrayudha MA, Petrus HT, Budhijanto W, Sulis- tyo H. 2017. Lithium recovery of spent lithium-ion battery using bioleaching from local sources microorganism. Ra- sayan Journal of Chemistry. 10(3):897–903. doi:10.7324/ RJC.2017.1031767.Joko S. 2020. Makalah ilmiah. 15:89–100.Li Q, Omar A, Cha-Umpong W, Liu Q, Li X, Wen J, Wang Y, Ra- zmjou A, Guan J, Taylor RA. 2020.  The potential of ho- llow fiber vacuum multi-effect membrane distillation for brine treatment. Applied Energy. 276(June):115437. doi: 10.1016/j.apenergy.2020.115437.Li X, Mo Y, Qing W, Shao S, Tang CY, Li J. 2019. Membrane- based technologies for lithium recovery from water lithi- um resources: A review. Journal of Membrane Science. 591(January):117317. doi:10.1016/j.memsci.2019.117317.Mustika PCBW, Astuti W, Sumardi S, Petrus HTBM, Sutijan. 2022. Separation Characteristic and Selectivity of Lithi- um from Geothermal Brine Using Forward Osmosis. Jo- urnal of Sustainable Metallurgy. doi:10.1007/s40831-022-00602-z.Natasha NC, Lalasari LH, Miftakhur R, Sudarsono JW. 2018. Ekstraksi Litium dari β – Spodumen Hasil Dekomposisi Batuan Sekismika Indonesia Menggunakan Aditif Natri- um Sulfat.Prawira J. 2017. Karakteristik Membran dan Pengaruhnya Ter- hadap Kinerja Proses Distilasi Membran. Delft University of Technology. 3(1):0–11. doi:10.5281/zenodo.1134034.Purnomo BJ, Pichler T. 2014.  Geothermal systems on the is- land of Java, Indonesia. Journal of Volcanology and Geo- thermal Research. 285:47–59. doi:10.1016/j.jvolgeores.2 014.08.004.Roobavannan S, Vigneswaran S, Naidu G. 2020.   Enhan- cing the performance of membrane distillation and ion- exchange manganese oxide for recovery of water and lithium from seawater. Chemical Engineering Journal. 396(May):125386. doi:10.1016/j.cej.2020.125386.Setiawan FA, Rahayuningsih E, Petrus HTBM, Nurpratama MI, Perdana I. 2019a. Kinetics of silica precipitation in geo- thermal brine with seeds addition: minimizing silica sca- ling in a cold re-injection system. Geothermal Energy. 7(1). doi:10.1186/s40517-019-0138-3.Setiawan H, Petrus HTBM, Perdana I. 2019b. Reaction kineti- cs modeling for lithium and cobalt recovery from spent lithium-ion batteries using acetic acid. International Journal of Minerals, Metallurgy, and Materials. 26(1):98– 107. doi:10.1007/s12613-019-1713-0.Siekierka A, Tomaszewska B, Bryjak M. 2018. Lithium cap- turing from geothermal water by hybrid capacitive deio- nization. Desalination. 436(February 2018):8–14. doi: 10.1016/j.desal.2018.02.003.Sujoto VSH, Sutijan, Astuti W, Mufakhir FR, Petrus HTBM. 2021. Lithium recovery from synthetic geothermal bri- ne using electrodialysis method. IOP Conference Seri- es: Earth and Environmental Science. 882(1):012003. doi: 10.1088/1755-1315/882/1/012003.Sujoto VSH, Sutijan, Astuti W, Sumardi S, Louis ISY, Petrus HTBM. 2022. Effect of Operating Conditions on Lithium Recovery from Synthetic Geothermal Brine Using Ele- ctrodialysis Method. Journal of Sustainable Metallurgy. 8(1):274–287. doi:10.1007/s40831-021-00488-3.Sutijan S, Wahyudi S, Ismail MF, Mustika PCB, Astuti W, Prase- tya A, Petrus HTBM. 2022. Forward osmosis to concentra- te lithium from brine: the effect of operating conditions (pH and temperature). International Journal of Techno- logy. 13(1):136. doi:10.14716/ijtech.v13i1.4371.Zhang Y, Peng Y, Ji S, Li Z, Chen P. 2015. Review of thermal effi- ciency and heat recycling in membrane distillation pro- cesses. Desalination. 367:223–239. doi:10.1016/j.desal.20 15.04.013.Zhao K, Heinzl W, Wenzel M, Büttner S, Bollen F, Lange G, He- inzl S, Sarda N. 2013. Experimental study of the memsys vacuum-multi-effect-membrane-distillation (V-MEMD) module. Desalination. 323:150–160. doi:10.1016/j.desal. 2012.12.003.